Determinants of contraceptive utilisation amongst teenage mothers: a case-control study in kyangwali refugee settlement (Uganda) - Lule, Herman; Echoru, Isaac; Nnabagulanyi, Mary; Mulumba, Richard (International Journal of Current Advanced Research, 2015)
The determinants of contraceptive utilisation amongst teenage mothers in refugee settings are poorly understood. To establish and compare determinants of contraceptive utilisation amongst refugee and host teenage mothers in Kyangwali Refugee Settlement, we conducted a case-control study to interview 132 cases and 264 controls made up of mothers aged 13-19 years during April 2014, using survey questionnaires and a focussed group discussion. Quantitative data was analysed using SPSS 16.0.Chi-square testing and Odds ratios at 95% confidence interval, and p<0.05 as significant were conducted to determine factors that significantly influenced contraceptive utilisation. Of the 396 teenage mothers, 64.6% (256) were refugees whereas 35.4% (140) were host nationals. Spousal support [X2=6.489, p=0.039; OR=2.250 (1.994-2.571) 95% CI], husband’ level of education [X2=16.189, p=0.000; OR=2.043(1.442-2.896) 95% CI] and a low birth order [X2=7.749, p=0.005; OR=1.227 (1.072-1.405) 95% CI] were significant determinants of contraceptive use. The major barriers contraception were fear of side effects 35.4% (140), refusal by the husband 30.3% (120) and lack of community based access 23.0% (91). There was no significant statistical difference in current use of contraceptives between refugee teenage mothers and host nationals [X2=0.138, p=0.710; OR=1.087(0.701-1.686) 95% CI].There is need to restructure delivery of contraceptive services in a way that enhances maximum uptake amongst teenage mothers in refugee settings, through integrated outreaches, girl-child education and male targeted messages in order to curtail the consequences of contraceptive underutilisation in this population.
Keywords: Case-Control; Contraceptive-Utilisation; Nationals; Refugees; Teenage-Mothers